Assessment of optimal specimen to measure the compressive strength of earthen-based masonry. (28th February 2023) - Lan, Guanqi; Weng, Guangyuan; Zhang, Kun
Graphical abstract: Highlights: The effect of the bonding arrangement and h / t ratio on the compression behavior of earthen-based masonry was studied. The optimum bonding arrangement of earthen-based masonry for compressive strength test is stretcher bonded. The optimum h / t ratio of earthen-based masonry for compressive strength test is 3/1–4/1. Abstract: The compressive strength of masonry is regarded as an essential primary mechanical parameter of this kind of structure. However, standard specimens used to test compressive strength of earthen-based masonry vary considerably in issued codes, which hinders the intercomparison of experimental results. In this study, two kinds of adobe and two kinds of new earthen bricks were selected for preparing masonry specimens. A series of uniaxial compression tests were performed to reveal the compression behaviors of several types of earthen-based masonry, while considering the influence of the specimen bonding arrangement and h/t ratio. Analytic hierarchical processes were used to evaluate the bonding arrangement and h/t ratio of earthen-based masonry specimens from operability, reproducibility, instrument, and equipment requirements for determining an optimal specimen with excellent comprehensive performance. The results showed that optimal specimens for compressive strength tests of different earthen-based masonry can use the same bonding arrangement and h/t ratio. The stretcher bonded specimen with a h/t ratio of 3/1–4/1 should be used as the optimal specimen for compressive strength testing of earthen-based masonry. The results can be used as a reference for establishing a simple and general compressive test method for earthen-based masonry.